(untitled) (Research, Society and Development, 2020)
The occurrence of water restriction is one of the environmental stresses that most limit soybean grain yield. Studies that seek to identify soybean cultivars with greater drought tolerance are important for agricultural production. This study was carried out with the purpose of evaluating the response of 22 soybean cultivars grown under adverse environmental conditions (irrigated and rainfed system), aiming to determine the best selection indexes to identify drought-tolerant soybean cultivars. Two experiments were carried out under field conditions in the municipality of Cassilândia (MS) during the 2018/2019 growing season, one in rainfed conditions with water restriction and the other in an irrigation system with central pivot. A randomized block design was used, in a 2 × 22 factorial scheme with three replications. The treatments consisted of two cultivation conditions (irrigated and rainfed system) and 22 soybean cultivars. From the data of grain yield in irrigated and rainfed systems, 12 drought tolerance indexes were estimated. The identification of soybean cultivars tolerant and/or susceptible to water restriction was carried out using different multivariate analysis methods (ranking method, hierarchical cluster analysis and principal component analysis). The 98R35 IRPO, RK 8317 IPRO and RK 8115 IPRO cultivars were classified as having greater drought tolerance, and are therefore the most suitable cultivars to be cultivated in Cerrado regions with water restriction. On the other hand, the TMG 7067 IPRO, M 5917 IPR, RK 6719 IPRO cultivars were classified as more susceptible to water restriction, and should not be recommended for cultivation in the region of Cassilândia (MS) under rainfed conditions in season with high probability occurrence of water deficiency. The indices of tolerance MP, STI, GMP and HM were the most indicated to identify soybean cultivars with greater tolerance to drought and with high grain yield potential in irrigated and rainfed systems in the region of Cassilândia, State of Mato Grosso do Sul.